DNA barcoding suggests hidden diversity within the genus Zenopsis (Zeiformes, Zeidae) - Florencia Matusevich; Valeria Gabbanelli; Gonzalo Vulcano; Natalia Plá; Victoria M. Lenain; Diego M. Vazquez; Juan M. Díaz de Astarloa; Ezequiel Mabragaña (Zoosystematics and Evolution, 2024)
Currently, the genus Zenopsis, also known as silver John Dory, comprises at least five valid species with a wide range of distribution. However, recent studies have proposed the existence of a new Zenopsis species inhabiting the Indian Ocean, and a preliminary search in the Barcode of Life Database reveals the presence of different barcode index numbers (BIN) for the nominal species Zenopsis conchifer. In the Southwest Atlantic Ocean (SWA), Z. conchifer is the only species reported so far. Therefore, the aim of this work was to evaluate, at the molecular level, the potential taxonomic diversity within the genus Zenopsis and to assess if the species occurring in the SWA corresponds with Z. conchifer. Using data available in worldwide genetic databases, a maximum likelihood tree, a BIN, and an automatic barcode gap discovery analysis were carried out. Additionally, specimens sampled from the SWA were morphologically compared with specimens from different parts of its distribution using available data. The specific identity at the molecular level of specimens occurring in the SWA was confirmed as Z. conchifer. The results of the molecular analysis highlight the existence of hidden specific diversity within the genus.